Effectiveness of Project-Based Learning Model on Students' Natural Science Learning Outcomes - Krestina Kusumawati; Tabitha Sri Hartati Wulandari (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2025)
This study aims to determine the effectiveness of the influence of the Project-Based Learning learning model on the learning outcomes of 9th-grade science students at Junior High School 5 Tuban. The type of research used is experimental research, and the research design is a one-group pretest-posttest Design. The population in this study was the ninth-grade students of SMP Negeri 5 Tuban as a whole, while the research sample was class IX-E students, totalling 31 students. The data collection techniques through learning outcome instruments include pretest and post-test scores. The data analysis techniques used are N-Gain Test analysis and descriptive analysis. The results showed that students' average score after applying the PjBL model increased by 29.03; in contrast, the results of the N-Gain analysis showed a value of 0.69 with a sufficient category. This study concludes that the effectiveness of the project-based learning (PjBL) model affects the results of students' natural science learning